WAYS TO FORM SOCIO-HOUSEHOLD QUALIFICATIONS OF CHILDREN WITH DOWN SYNDROME - Makhmudova Madinakhon Sobirkhonovna; Shokirova Rayhana; Odilova Maftuna (Galaxy International Interdisciplinary Research Journal, 2023)
Formation of socio-domestic qualifications in students with Down syndrome areas of work, specialized auxiliary school, in boarding schools, information is described on the formation of knowledge, skills and qualifications that students with Down syndrome have at school.